2022
DOI: 10.1021/acs.langmuir.1c02312
|View full text |Cite
|
Sign up to set email alerts
|

Interphase Protein Layers Formed on Self-Assembled Monolayers in Crowded Biological Environments: Analysis by Surface Force and Quartz Crystal Microbalance Measurements

Abstract: We investigated a viscous protein layer formed on self-assembled monolayers (SAMs) in crowded biological environments. The results were obtained through force spectroscopic measurements using colloidal probes and substantiated by exhaustive analysis using a quartz crystal microbalance with an energy dissipation technique. A hydrophobic SAM of n-octanethiol (C8 SAM) in bovine serum albumin (BSA) solution is buried under an adlayer of denatured BSA molecules and an additional viscous interphase layer that is fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…We previously reported that a layer of denatured protein molecules with a thickness of about 10 nm is formed on protein-adsorbing surfaces. 55 We concluded that this layer resulted in the local change in the refractive index at the interface.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We previously reported that a layer of denatured protein molecules with a thickness of about 10 nm is formed on protein-adsorbing surfaces. 55 We concluded that this layer resulted in the local change in the refractive index at the interface.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…Therefore, the difference in the response in serum (between 0 and 540 s) is due to the difference in the accumulation and conformational change of the protein molecules. We previously reported that a layer of denatured protein molecules with a thickness of about 10 nm is formed on protein-adsorbing surfaces . We concluded that this layer resulted in the local change in the refractive index at the interface.…”
Section: Resultsmentioning
confidence: 87%
“…A viscous protein layer formed over self-assembled monolayers (SAMs) was investigated by Mondarte et al [ 42 ] in a BSA-crowded biological environment. The researchers used two SAM layers—one composed of 1-octane thiol (C8 SAM) and the second composed of zwitterionic sulfobetaine (SB)-terminated alkanethiol (SB SAM).…”
Section: Biological Sensorsmentioning
confidence: 99%
“…It is well known that protein adsorption from HS onto solid surfaces has complex kinetics with faster adsorbing components with low affinity gradually being replaced by more slowly adsorbing species with high affinity (Vroman effect , ). Also, for the incubation times with the coating proteins used in Figure , coating formation had stabilized almost, but not completely yet.…”
Section: Resultsmentioning
confidence: 99%